Efeitos da urbanização na nidificação de duas espécies simpátricas de formigas do gênero Crematogaster - Nogueira, Gabriel da Costa (2024)
The structure of ant colonies varies greatly depending on the number of nests andqueens. These variations have important functional and ecological effects, allowingsome species to successfully occupy heavily altered urban environments.Furthermore, variations in the number of queens and nests per colony define the levelof gene sharing within the colony and consequently the balance between conflict andcooperation. In this study, we used two sister species, but with differences in theircolonial structure, Crematogaster abstinens, (monogynous and monodomous) andCrematogaster pygmaea (polygynous and polydomous) to investigate the potentialeffects of urbanization on their founding strategies. To this end, we carried out mappingof nests and collections of workers in nine areas of different cities in the state of Ceará.To verify the quality of vegetation cover (level of urbanization), the NDVI was calculatedin different ranges based on the nest collection and mapping quadrant (50 m, 100 m,200 m) per location, for the last six years ( 2018-2023). In 89.1% of the locations therewas a drop in NDVI values, showing that the advance of urbanization has negativelyaffected the vegetation and positively the number of ants. The two species showedspatial segregation and a high spatial aggregation of nests. The study provides newinformation and a general overview of the loss of vegetation cover, this degradationscenario has enabled the entry of invasive species and the extinction of native species.